Reactive hypertrophy of an accessory spleen mimicking tumour recurrence of metastatic renal cell carcinoma - Tjaden, Christin; Werner, Jens; Büchler, Markus W.; Hackert, Thilo (Asian journal of surgery, 2011)
De novo occurrence of an accessory spleen after splenectomy is worth noting for two reasons. First, it is known that splenectomy can cause reactive hypertrophy of initially inactive and macroscopically invisible splenic tissue. Second, it can mimic tumour recurrence in situations in which splenectomy has been performed for oncological reasons. This might cause difficulties in differential diagnosis and the clinical decision for reoperation. We report the case of a patient with suspected recurrence of renal cell carcinoma after total pancreatectomy and splenectomy for metastatic renal cell carcinoma, which finally revealed an accessory spleen as the morphological correlate of the newly diagnosed mass in the left retroperitoneum.
Gesehen am 09.11.2022